GIS MODELLING OF SOLAR POTENTIAL IN TOPLICA REGION - Valjarevic, Aleksandar (Bulletin of Natural Sciences Research, 2016)
In this paper we investigated possible potential solar area on Toplica region based on GIS (Geographical Information system) and using a special kriging method with the help of open sources GIS software Quantum GIS. This kriging method is very special to vectorized and calculated the small area. The statistical approach calculated between datasets of three meteorological stations (Niš, Prokuplje, Kuršumlija). Data using of insolation from that meteorological stations from the period of (1953-2013) is useful for a solution to calculating solar potential. The also used parameter is hypsometry of relief of the whole area of Toplica region. Area of Toplica region is 2.231 km2 with a population of 90600 citizens. Divided into fourth municipalities (Prokuplje, Žitoradja, Black, Kuršumlija). The GIS modeling indicates that ideal areas for solar development are located the potential places in Toplica region. Only 13.6 km2 of the head model scores that were in the 90-100% range. However, given the statewide high insolation values with minimal variance, solar projects may be better suited for small-scale residential or commercial projects.